2017
DOI: 10.5507/bp.2017.011
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced breast cancer in elderly patients

Abstract: Background. Although locally advanced breast cancer (LABC) is more common in the elderly population, there is little data on the clinical characteristics and survival of these patients. The aim of the present study was to compare different factors affecting survival in elderly patients with LABC. Methods. Retrospective analysis was carried out on a cohort of 80 patients aged 70 to 96 years, diagnosed with LABC defined as T3 N1, T4 N0, any N2 or N3, and M0. The prognostic impact of selected clinical parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…It showed that patients who were ≥80 years had a worse OS, with a median of 31.6 months (19.0-44.3) (HR 2.55, 95% CI 1.40-4.65, P = 0.002), than did patients who were <80 years, with a median of 78.5 months (51.4-105.5). Moreover, multivariate analysis also confirmed the significance of older age on OS in patients in the group who were ≥80 years (HR 4.76, 95% CI 1.22−18.61, P = 0.025) [ 17 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It showed that patients who were ≥80 years had a worse OS, with a median of 31.6 months (19.0-44.3) (HR 2.55, 95% CI 1.40-4.65, P = 0.002), than did patients who were <80 years, with a median of 78.5 months (51.4-105.5). Moreover, multivariate analysis also confirmed the significance of older age on OS in patients in the group who were ≥80 years (HR 4.76, 95% CI 1.22−18.61, P = 0.025) [ 17 ].…”
Section: Discussionmentioning
confidence: 87%
“…Data in the literature about the impact of a patient's age on the prognosis of BC are contradictory. Some authors reported that younger patients have a worse prognosis, whereas other authors reported elderly patients as having the worst prognosis [15][16][17][18][19][20][21]. Moreover, previous data in the United States, the United Kingdom, and KSA did not show any significant impact of patient age on OS and progression-free survival (PFS) in LABC [9,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, LABC is still predominantly multidisciplinary comprehensive treatment, 1 , 2 , 11 , 19 yet this pattern is not going well in elderly patients. 7 First, elderly patients were not suitable for surgery or difficult to operate immediately because of their age, medical comorbidities or poor compliance, and even if they underwent surgery, complications such as upper limb edema could cause great suffering. 7 Although radiotherapy and chemotherapy were effective in elderly LABC, they were sometimes abandoned because they were poorly tolerated or mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these parameters holds the potential to affect decision for treatment in a facility with or without DKG-certi cate, beyond that multifactor interaction needs to be considered. For instance, elderly women with breast cancer present more frequently with advanced disease [13]. Thus, adjusted logistic regression was performed to take potential interaction between all analyzed parameters into account.…”
Section: Introductionmentioning
confidence: 99%